Effective Use Of Learning Applications For English Subjects In Elementary School - Nurniati, Emi; Prasetyo Irianto, Dhaniel; Syah Putra, Arman; Susanti, Daru; Zikriah, Zikriah; Nurhayati, Nurhayati; Aisyah, Nurul (CV. Inara, 2022)
The background of this research is to know the effectiveness of the variables raised in this research. The variables raised in this research are online learning application variables and English subject variables and Elementary School variables. These variables influence each other and have a significant effect. The method used in this research is quantitative method, using a survey of 100 parents of students who use the application for learning English subjects. The problem raised in this research is how the use of applications can be more effective than learning directly or offline by using the application. It is hoped that it can help students who do not understand better understand because with this application they can repeat the lessons they have learned at school so that they can improve their learning. Student scores at the time of the exam. The purpose of this study is to find out the extent to which the effectiveness of an application that will be applied to a subject in elementary school with the application, it can be concluded that this research results in the application having a very significant effect on the teaching and learning system in elementary schools, especially English subjects.